2020
DOI: 10.3390/w12041001
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Model for the Evaluation of Groundwater Recharge Based on the Concept of Conservative Use Potential: A Study in the River Pandeiros Watershed, Minas Gerais, Brazil

Abstract: Water resources have been increasingly impacted due to the growth of water demand associated with environmental degradation. In this context, the mapping of groundwater recharge potential has become attractive to water managers as it can be used to direct public policies and conserve this natural asset. The present study modifies (improves) a spatially explicit model to determine groundwater recharge potential at the catchment scale, testing it in the Pandeiros River basin located in the state of Minas Gerais,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…A high association between humidity and land use can be due to a large area of agricultural fields in the study zone. Studies have demonstrated that the zones with high groundwater recharge potential are located in areas with dense vegetation cover coupled with flat relief and consolidated and structured soils [126].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…A high association between humidity and land use can be due to a large area of agricultural fields in the study zone. Studies have demonstrated that the zones with high groundwater recharge potential are located in areas with dense vegetation cover coupled with flat relief and consolidated and structured soils [126].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The correct characterization of this hydrological process is fundamental to integrated water resources management [1][2][3][4][5][6][7], although it is complex and difficult to quantify [8][9][10]. Temporal and spatial variability adds to the lack of data and resources, which prevents the actions taken by managers and researchers from being correctly fulfilled when facing scenarios of overexploitation, inordinate land use, pollution, and other environmental damage [11][12][13][14]. Depending on the particularities of a region, the extent of the groundwater recharge process can go beyond even national political and administrative borders [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Some methods, for example, those based on flow direct measurements, can generate good results when obtaining point values, but may be unable to characterize the spatial variability of the process. Distributed methods are typically avoided due to the amount and variety of data required [7,12,13,29]. This methodological difficulty is not restricted to groundwater recharge research, and a way to overcome it is through the adoption of an experimental watershed as the study area.…”
Section: Introductionmentioning
confidence: 99%
“…In the rural environment, the alternatives comprise the storage of rainwater in small dam lakes (rainwater harvesting), to be used in the irrigation of cropland or combating wildfires [19,20]. In the urban environment, especially around the large metropolises, the conjunctive use of various sources (surface water, groundwater, desalinized water and recycled wastewater) can be a reliable path to adaptation, aided by controlled groundwater recharge where possible [21][22][23][24][25]. The incentive to produce clean drinking water in headwater catchments through the adaptation of land uses (e.g., a shift from extensive monocultures to agro-forestry systems), aiming at the reduction of treatment and hence final costs, is a promising adaptation measure.…”
mentioning
confidence: 99%